Speculum Observation and Trajectory Measurement in Gas Extraction Drilling: A Case Study of Changling Coal Mine - Enbiao Zhao; Kangnan Li; Xin Yang; Nan Deng (Geofluids)
Coal will still be China’s basic energy for quite a long time. With the increase of mining depth, gas content and pressure also increase. The problems of gas emission and overrun affect the safety and efficient production of coal resource to a certain extent. In this work, the field test of gas drainage borehole peeping and trajectory measurement in coal seam of Changling coal mine are carried out. These coal seams include C5b coal seam, upper adjacent C5a coal seam, C6a coal seams, C6c in lower adjacent strata, and C5b coal seam in high-level borehole. The view of gas drainage borehole peeping and trajectory measurement in the working seam, upper adjacent layer, lower adjacent layer, and high position are obtained. It is found that the hole collapses at the position of about 20 m in both adjacent strata and high-level boreholes, and there are a lot of cracks in the high-level boreholes before 12 m. The deviation distance of high-level borehole is large, and the actual vertical deviation of upper adjacent layer is small. Finally, the strategies to prevent the deviation of drilling construction are put forward. It includes four aspects: ensuring the reliability of drilling equipment, reasonably controlling the drilling length, standardizing the drilling, and reasonably selecting the drilling process parameters.